2014
DOI: 10.4236/ojg.2014.410037
|View full text |Cite
|
Sign up to set email alerts
|

Do U/Pb-SHRIMP Dating and Pb Stepwise Leaching (PbSL) Analyses Confirm the Lack of Precambrian Basement Outcrops in Thailand?

Abstract: U/Pb-SHRIMP dating and Pb stepwise leaching (PbSL) experiments on zircons and garnets, respectively have confirmed the lack of Precambrian outcrops within the crystalline basement of Thailand. The obtained data for the high grade metamorphism show Indosinian ages ranging from 225-200 Ma as previously suggested for the vast majority of outcrops in NW-Thailand ([1] and references therein), as well as a small group of ages in the range of 445 Ma in the Lampang Province. Further, the age of a thermal imprint aroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“… εNd (t) against initial Sr (Fig. 5c in [1] ) Sibumasu [37] Indochina [46] , [50] , [51] Sukhothai including Lincang and Chanthaburi [42] , [44] , [48] , [49] , [52] , [53] , [54] , [55] , [56] , [57] Inthanon Zone including Bentong Raub [44] , [47] , [49] Lhasa [58] Truong Son [59] , [60] Lead [41] , [59] , [61] , [62] , [63] . 207 Pb/ 204 Pb (i) against 206 Pb/ 204 Pb (i) (Fig.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… εNd (t) against initial Sr (Fig. 5c in [1] ) Sibumasu [37] Indochina [46] , [50] , [51] Sukhothai including Lincang and Chanthaburi [42] , [44] , [48] , [49] , [52] , [53] , [54] , [55] , [56] , [57] Inthanon Zone including Bentong Raub [44] , [47] , [49] Lhasa [58] Truong Son [59] , [60] Lead [41] , [59] , [61] , [62] , [63] . 207 Pb/ 204 Pb (i) against 206 Pb/ 204 Pb (i) (Fig.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“… 207 Pb/ 204 Pb (i) against 206 Pb/ 204 Pb (i) (Fig. 5d in [1] ) Grid of εNd (t) including converted εHf (t) [Published data from [9] , [37] , [38] , [40] , [44] , [46] , [48] , [49] , [51] , [52] , [55] , [60] , [64] , [65] , [66] , [67] ]. (Fig.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…1), was inferred as being evidence for Pan-African aged crustal reworking of Sibumasu basement prior to break up of Gondwana. Within the Sukhothai zone, Hansen et al (2014) reported a SHRIMP age of 445 ± 3.8 Ma from the Muang Pan Gneiss, sited east of the Chiang Rai Line in Lampang Province. These data all imply that the basement for both Sibumasu and the Sukhothai Arc have yielded similar early Palaeozoic ages.…”
Section: Is the Chiang Rai Line A Suture?mentioning
confidence: 98%